Detoxification of Olive Mill Wastewaters by Fenton’s Process - Domingues, Eva (2018)
Olive mill wastewaters (OMW) constitute an environmental problem affecting mainly Mediterranean Sea area countries where the olive mill industry is a very important economic sector. The strong impact and management issues of these effluents are mainly due to their seasonality, localized production, and high organic load with high toxic features and low biodegradability. As the olive oil industry is highly water demanding, the search for suitable water recovery strategies requires the development and optimization of advanced treatment technologies. The classical Fenton’s process is an interesting alternative, as it operates at room conditions of pressure and temperature. However, it shows some drawbacks, such as the generation of iron sludges, which require further management. Nevertheless, because of its features that make it industrially desirable, overcoming these limitations has been the focus of researchers in the last years. Bearing this in mind, this paper focuses on the recent research regarding OMW treatment using Fenton’s process. The use of Fenton’s peroxidation treatment at homogenous, heterogeneous, and photo-aided conditions is analysed. The use of solid catalysts may be an interesting way to avoid sludge formation. Light-driven Fenton can also reduce the amount of iron needed for effective degradation. Moreover, Fenton’s process integration in combined treatment schemes is discussed. Finally, remarks regarding its application at full scale are given.